Analisis SWOT Pada Strategi Pemasaran Produk Simpanan Kurban Di KSPPS BMT NU Sejahtera Cabang Jepara - Muyassarah Muyassarah (LPMP Imperium, 2019)
Purpose-The purpose of this research is to introduce the product to the people of Jepara to participate in the